PENGARUH TEKANAN BAHAN BAKAR TERHADAP EMISI GAS BUANG PADA MESIN K3-VE - Arizal, Heru; Ramadani, Ali Hasbi; Abdi, Ferly Isnomo (Otopro, 2020)
One of the causes of air pollution today is the increasing use of motorized vehicles. The use of technology has also been pinned on many wrong vehicles to improve the quality of the exhaust emissions that have been produced. One of them is EFI (Electronic Fuel Injection) technology which has been embedded in many vehicles. The component that has an effect on improving the quality of exhaust emissions at EFI is an electronic fuel pump. The fuel pressure on the electronic pump can be adjusted manually. This study aims to determine changes in fuel pressure on exhaust gas emission levels. This research uses an experimental method, where the fuel pressure is varied from the pressure of 50psi, 40psi, 30psi and 20psi, and the engine speed is varied from 800rpm, 1500rpm, 2250rpm, 3000rpm and 3750rpm. The results of the data obtained are analyzed using the quantitative description method. The test results showed that there was a decrease in the lowest CO level of 0.663% at 30psi fuel pressure with 3750rpm engine speed. HC also experienced a decrease, the lowest decrease was obtained in the value of 280ppm at 20psi fuel pressure and 3750rpm engine speed. While CO2 has increased, the highest increase of 13.33% was achieved at 20psi fuel pressure and 3750rpm engine speed.